The Ricardian Equivalence in Times of Covid-19: A Case of Indonesia and Malaysia - Mohammad Bintang Pamuncak; Diva Azka Karimah; Ihsanul Ikhwan (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study aims to seek the validity of Ricardian equivalence in Indonesia and Malaysia using Autoregressive Distributed Lag (ARDL). This study finds the invalidity of Ricardian equivalence in the long-term and short-term in both countries. For Indonesia case, during the last three financial crisis happens in 1998, 2008, and 2020 caused by COVID-19, Ricardian equivalence happens only in 1998. More interestingly, this study finds that there is a different relationship between household savings and household expenditure in Indonesia and Malaysia. This study is expected to contribute to the development of body of knowledge, particularly with the case of Ricardian equivalence and Keynes approaches on expansionary fiscal policy as well as practical public policy, particularly related to government budget in crisis and household saving and expenditure.